Historyczna ewolucja independentyzmu katalońskiego. Formowanie się katalonizmu poprzez działalność regionalnych ruchów społecznych - Chmura, Sylwia (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article contains an analysis of the historical development of Catalan nationalism, its evolution from the early Middle Ages to modern times. It points to the key role of social movements in the political process of protecting the Catalan identity from being degraded or completely eliminated by the Spanish central government. The depth of the region’s history points to several basic conclusions. Mainly, the image of Catalan separatism as a temporary “rush” of citizens, shaped by Catalan’s modern political elite to divert attention from the corruption scandals is untrue. The analysis of the rich history of Catalan political culture indicates that the phenomenon of Catalanism has become a constant.
Keywords: Katalonia; katalonizm; niepodległość; ruchy społeczne; protest; manifestacja; nacjonalizm